Agriculture & Resources Quarterly. (Canberra, Australia Australian Bureau of Agricultural and Resources Economics, 1989)
Devoted to disseminating the broader research findings and commodity outlook work of the Australian Bureau of Agricultural and Resource Economics (ABRE).
Quarterly
Previously issued as: Review of the Rural Economy and Resource Trends